1990
DOI: 10.1093/carcin/11.10.1837
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship within a series of okadaic acid derivatives

Abstract: Okadaic acid (OA) is a potent non-12-O-tetradecanoyl-phorbol-13-acetate (non-TPA) type tumor promoter on mouse skin. OA acts on cells through inhibiting the activity of protein phosphatases and results in the increase of phosphorylation of proteins. Seventeen OA derivatives were evaluated as possible tumor promoters by means of three biochemical tests: inhibition of specific [3H]OA binding to a particulate fraction of mouse skin containing protein phosphatases, inhibition of protein phosphatase activity, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…2). In our structure, the acid motif in OA accepts a hydrogen bond from the hydroxyl group of Tyr-272 (20). Other hydrogen bonding interactions occur between Arg-96 and the C-2 hydroxyl of the inhibitor and between Arg-221 and the C-24 hydroxyl group of OA.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…2). In our structure, the acid motif in OA accepts a hydrogen bond from the hydroxyl group of Tyr-272 (20). Other hydrogen bonding interactions occur between Arg-96 and the C-2 hydroxyl of the inhibitor and between Arg-221 and the C-24 hydroxyl group of OA.…”
Section: Resultsmentioning
confidence: 93%
“…The importance of the hydrogen bond between Tyr-272 and the acid group of OA is exemplified by the observation that esterification or removal of the acidic moiety in OA results in elimination of its inhibitory activity and by the fact that mutation of Tyr-272 to Phe results in a 50-fold increase in the K i value (20,22). Despite the intimate interaction of the C-2 hydroxyl group of OA with the Arg-96 side chain, removal of the hydroxyl group results in only a 7-fold increase in the K i value (24).…”
Section: Discussionmentioning
confidence: 99%
“…Methyl okadaate (MeOk) is a methyl ester derivative of the OA, artificially produced in the laboratory, but also found in shellfish, and even in naturally collected or cultured dinoflagellates from the genera Prorocentrum and Dinophysis (Hu et al, 1992;Vale and Sampayo, 1999;Suzuki et al, 2004;Suarez-Gomez et al, 2005). Usually, MeOk has been considered as an inactive molecule because of its low activity in inhibiting PPs (Nishiwaki et al, 1990;Takai et al, 1992). However, recent studies indicated that MeOk induced reorganization of the actin cytoskeleton of human neuroblastoma cells (Vilarino et al, 2008), and although the potency of MeOk was lower than that of OA, its mechanism of action was unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilized MC-LR has been used to affinity purify PP2A [21]. However, the binding capacity (3 ,ug PP2A/l mg MC-LR) was only 0.03% of that ex-petted, probably because coupling to the matrix involved one of the MC-LR carboxyl groups that is important for binding to PP2A [22].…”
Section: Introductionmentioning
confidence: 99%